Fluoride toothpaste supplemented with sodium hexametaphosphate reduces enamel demineralization in vitro - da Camara, Danielle Mendes [UNESP]; Pessan, Juliano Pelim [UNESP]; Francati, Tamires Melo [UNESP]; Souza, José Antonio Santos [UNESP]; Danelon, Marcelle [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP] (My University, 2016)
Objective: The aim of this study was to evaluate the effect of fluoride dentifrices combined with sodium hexametaphosphate (HMP) on enamel demineralization in vitro. Material and methods: Enamel bovine blocks were selected by initial surface hardness (SHi) and then divided into five experimental groups (n = 12): placebo (without fluoride and without HMP); 1100 ppm F (1100F); and 1100F associated with HMP at 0.5 % (1100HMP0.5%), 1 % (1100HMP1%), and 2 % of HMP (1100HMP2%). Blocks were submitted to five pH cycles (demineralizing/remineralizing solutions) at 37 °C. After pH cycling, final surface hardness (SHf), percentage of surface hardness loss (%SH), integrated differential hardness (ΔIH), integrated loss of subsurface hardness (ΔKHN), and enamel firmly bound fluoride (F) were determined. Data were submitted to one-way ANOVA, followed by Student–Newman–Keuls test (p < 0.05). Results: Significant differences were observed among all groups regarding %SH and ΔKHN. 1100HMP1% promoted the lowest mineral loss among all groups (p < 0.001), and led to significantly lower demineralization in the deeper regions of the subsurface lesion when compared with the other HMP-containing toothpastes (p < 0.001). Significantly higher mineral loss was observed for 1100HMP2% when compared to the other fluoridated dentifrices, mainly in the outer part of the lesion (p < 0.001). Enamel F uptake was similar for 1100F and 1100HMP1% but significantly reduced for other HMP concentrations. Conclusion: The supplementation of a 1100-ppm F dentifrice with 1 % HMP promoted a higher inhibitory effect against enamel demineralization when compared to a dentifrice containing the same amount of fluoride in vitro. Clinical relevance: This dentifrice could potentially be indicated to patients at high risk of caries.
Keywords: Demineralization; Dental enamel; Dentifrices; Fluorides; Polyphosphates